Silicon-carbon composite material, preparation method thereof, pole piece and application

By introducing a manganese source during the preparation of silicon-carbon composite materials, the directional distribution of manganese atoms in the porous carbon pores is used to solve the problems of silane deposition and poor carbon layer coating, and the cycling performance of lithium-ion batteries is significantly improved.

CN119725491AActive Publication Date: 2025-03-28SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411981027.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the preparation process of silicon-carbon composite materials in the prior art, the controlled deposition of silane and the degree of coating of the carbon layer are poor, resulting in poor circulation performance of the produced battery.

Method used

When preparing silicon-carbon composite materials, manganese source is introduced, and manganese atoms in the composite template agent are distributed in the porous carbon channels to improve the deposition efficiency of silane deposition and vapor phase carbon coating.

Benefits of technology

The silicon-carbon composite battery produced by this method has better cycling performance, which significantly improves the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material, a preparation method thereof, a pole piece and application. The preparation method of the silicon-carbon composite material comprises the following steps: S1, sequentially performing carbonization treatment and reduction reaction on a mixture A to obtain porous carbon; the mixture A comprises a carbon matrix and a composite template agent; the composite template agent comprises a mixed solution of a first template agent and a manganese source; the specific surface area of the porous carbon is 1600-2200m < 2 > / g; and S2, sequentially carrying out silane deposition and gas-phase carbon coating on the porous carbon. The manganese source is introduced when the silicon-carbon composite material is prepared, so that the deposition of silane and the coating of the carbon layer can be well controlled. A battery prepared from the prepared silicon-carbon composite material has relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method, a pole piece and application thereof. Background Art

[0002] In order to solve the mileage anxiety of new energy vehicles, the demand for high-energy-density lithium-ion batteries has increased significantly. Compared with traditional graphite negative electrodes (372mAh / g), silicon has a higher theoretical specific capacity (4200mAh / g). Therefore, the application of silicon-based negative electrodes can greatly improve the energy density of lithium-ion batteries, but silicon-based negative electrodes often have a large volume expansion during the charging and discharging process. The large volume expansion often leads to particle breakage, and the SEI film is regenerated on the surface of the broken particles, resulting in a significant reduction in the cycle life of the battery cell.

[0003] Therefore, silane is often vapor-deposited in the pores of porous carbon, and the volume expansion of the silicon-based negative electrode is suppressed through the confinement effect of the porous carbon, thereby increasing the cycle life of the battery cell. In the process of vapor deposition and carbon coating, the controllable deposition of silane and the uniform coating of the carbon layer largely determine the electrochemical properties, especially the cycle performance, of the battery made of silicon-carbon materials. In the prior art, the cycle performance of the battery made of silicon-carbon composite materials needs to be improved due to the poor control of the controllable deposition of silane and the coating degree of the carbon layer. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defect that the controllable deposition of silane and the coating degree of the carbon layer in the preparation process of the silicon-carbon composite material in the prior art are not well controlled, resulting in poor cycle performance of the battery obtained therefrom, and provide a silicon-carbon composite material and its preparation method, pole piece and application. The present invention can well control the deposition of silane and the coating of the carbon layer by introducing a manganese source when preparing the silicon-carbon composite material. The battery obtained by the obtained silicon-carbon composite material has better cycle performance.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:

[0007] S1. Carbonizing and reducing the mixture A in sequence to obtain porous carbon; the mixture A comprises a carbon matrix and a composite template; the composite template comprises a mixed solution of a first template and a manganese source; the specific surface area of ​​the porous carbon is 1600-2200 m 2 / g;

[0008] S2. sequentially subjecting the porous carbon to silane deposition and vapor phase carbon coating.

[0009] In S1 of the present invention, the type of the carbon matrix can be conventional in the art, preferably comprising phenolic resin and / or asphalt, such as phenolic resin.

[0010] Wherein, when the carbon matrix is ​​a phenolic resin, the preparation method of the phenolic resin can be obtained by conventional methods in the art, preferably comprising the following steps: mixing resorcinol, formaldehyde, ammonia water, ethanol and water, and performing a polymerization reaction.

[0011] Wherein, the mass volume ratio of the resorcinol to formaldehyde is preferably 80g:(100-140)mL, for example 80g:120mL. The mass ratio of the resorcinol to the ammonia water is preferably (1-3):1, for example 2:1. The mass ratio of the resorcinol to the ethanol is preferably (70-90):990, for example 80:990. The mass ratio of the resorcinol to the water is preferably 80:(6500-7500), for example 80:6930. The temperature of the polymerization reaction is preferably 90-110°C, for example 100°C. The time of the polymerization reaction is preferably 20-30h, for example 24h.

[0012] Wherein, when the resorcinol, formaldehyde, ammonia water, ethanol and water are mixed, it is preferred that water, ethanol and ammonia water are first mixed and stirred for the first time, then mixed with resorcinol for the second time, stirred for the second time, and then mixed with formaldehyde for the third time and stirred for the third time. The temperature of the first mixing may be 30°C. The speed of the first stirring is preferably 700-900r / min, for example, 800r / min. The time of the first stirring is preferably 20-40min, for example, 30min. The temperature of the second mixing may be 30°C. The speed of the second stirring is preferably 700-900r / min, for example, 800r / min. The time of the second stirring is preferably 5-15min, for example, 10min. The temperature of the third mixing may be 30°C. The speed of the third stirring is preferably 700-900r / min, for example, 800r / min. The time of the third stirring is preferably 20-30h, for example, 24h.

[0013] In S1 of the present invention, the type of the first template can be conventional in the art, preferably including one or more selected from Pluronic F-127, Synperonic F-108, Pluronic F-68, hexadecyltrimethylammonium bromide and sodium dodecyl sulfate, such as hexadecyltrimethylammonium bromide.

[0014] In S1 of the present invention, the type of the manganese source is preferably manganese oleate and / or manganese chloride, for example, manganese oleate or manganese chloride.

[0015] In S1 of the present invention, the method for preparing the composite template is preferably carried out through the following steps: mixing an aqueous solution of the first template and a manganese source under nitrogen conditions, and stirring.

[0016] The stirring temperature may be 50-70° C., for example, 60° C. The stirring time may be 5-7 h, for example, 6 h.

[0017] In S1 of the present invention, in the composite template, the mass concentration of the first template may be 6%-15%, preferably 6.66%-14%, such as 9%, 10%, 11% or 13.3%. The mass concentration of the manganese source may be 5%-20%, preferably 8%-12%, such as 9%, 10% or 11%.

[0018] In S1 of the present invention, in the composite template, the mass ratio of the first template to the manganese source may be (0.5-2):1, preferably (0.66-1.5):1, for example 1:1 or 1.33:1.

[0019] In S1 of the present invention, the mass ratio of the carbon matrix to the composite template may be (300-700):1, for example, 400:1, 500:1 or 600:1.

[0020] In S1 of the present invention, the temperature of the carbonization treatment may be 600-1000°C, such as 700, 800 or 900°C.

[0021] In S1 of the present invention, the carbonization treatment time may be 1-5 hours, for example 3 hours.

[0022] In S1 of the present invention, during the carbonization process, the first template will be decomposed and removed.

[0023] In S1 of the present invention, after the carbonization treatment and before the reduction reaction, a step of carbon dioxide activation is preferably further included.

[0024] The activation temperature of carbon dioxide is preferably 800-1000°C, such as 900°C.

[0025] Wherein, during the carbon dioxide activation, the flow rate of carbon dioxide can be 20-40 L / min, for example, 30 L / min.

[0026] The activation time of carbon dioxide is preferably 6-10 hours, such as 8 hours.

[0027] The mass volume ratio of the carbon matrix and the carbon dioxide is preferably 1 g:(1-2)L, for example 1 g:1.44L.

[0028] In S1 of the present invention, a reducing agent is generally added during the reduction reaction. The type of the reducing agent may be conventional in the art, such as a hydrogen-nitrogen mixture. In the hydrogen-nitrogen mixture, the volume concentration of hydrogen is preferably 1%-5%, such as 3%. The mass volume ratio of the carbon matrix and the reducing agent may be 10kg:(20-30)L, such as 10kg:27L.

[0029] In S1 of the present invention, the reduction reaction time may be 3-7 hours, for example 5 hours.

[0030] In S1 of the present invention, the specific surface area of ​​the porous carbon is preferably 1650-2100m 2 / g, such as 1811, 1824, 1807, 1795, 1487, 2015, 2088, 1701, 1664, or 1703m 2 / g.

[0031] In S2 of the present invention, the silane deposition operation may be conventional in the art, for example, performed in a rotary kiln.

[0032] In S2 of the present invention, the temperature of the silane deposition may be 400-600°C, for example 500°C.

[0033] In S2 of the present invention, the silane deposition time may be 10-14 hours, for example 12 hours.

[0034] In S2 of the present invention, when the silane is deposited, the type of silicon source gas used can be conventional in the art, such as monosilane.

[0035] In S2 of the present invention, the rate of heating from room temperature to the temperature for silane deposition may be 3-7° C. / min, for example, 5° C. / min.

[0036] In S2 of the present invention, a carrier gas is preferably introduced during the silane deposition. The type of the carrier gas is preferably nitrogen. The volume ratio of the carrier gas to the silicon source gas during the silane deposition can be 1:(1-3), for example 1:2.

[0037] In S2 of the present invention, the mass volume ratio of the porous carbon to the silicon source gas for silane deposition may be 1 g:(1-2) L, for example, 1 g:1.44 L.

[0038] In S2 of the present invention, the gas phase carbon coating operation may be conventional in the art, and is preferably carried out in a rotary kiln.

[0039] In S2 of the present invention, the temperature of the gas phase carbon coating may be 400-600°C, for example 550°C.

[0040] In S2 of the present invention, the gas phase carbon coating time may be 2-6 hours, for example 4 hours.

[0041] In S2 of the present invention, the type of the carbon source gas used in the gas-phase carbon coating may be one or more of methane, acetylene, ethylene and propylene, such as acetylene.

[0042] In S2 of the present invention, a carrier gas is preferably introduced during the gas phase carbon coating. The type of the carrier gas is preferably nitrogen. The volume ratio of the carrier gas to the carbon source gas during the gas phase carbon coating can be 1:(1-3), for example 1:2.

[0043] In S2 of the present invention, the mass volume ratio of the porous carbon and the carbon source gas coated with the gas phase carbon may be 1g:(0.1-1)L, for example, 1g:0.24L.

[0044] In the present invention, the applicant discovered during the research and development process that when a manganese source is added to the composite template, as the template forms pores, manganese atoms will be directionally introduced into the pores, thereby improving the deposition efficiency of silane deposition and vapor-phase carbon coating.

[0045] The present invention also provides a silicon-carbon composite material, which is prepared by the preparation method of the silicon-carbon composite material as described above.

[0046] The present invention also provides a silicon-carbon composite material having a core-shell structure, comprising a core and an outer shell, wherein the outer shell covers the core; the core comprises porous carbon, silicon and manganese; the specific surface area of ​​the porous carbon is 1600-2200 m 2 / g; the silicon and manganese are distributed in the pores of the porous carbon; and the shell includes a carbon coating layer.

[0047] In the present invention, the specific surface area of ​​the porous carbon is preferably 1650-2100m 2 / g, such as 1811, 1824, 1807, 1795, 1487, 2015, 2088, 1701, 1664, or 1703m 2 / g.

[0048] In the present invention, the mass content of manganese in the silicon-carbon composite material may be 0.3%-1.5%, for example, 0.74%, 0.31%, 0.94%, 1.21%, 0.69%, 0.65%, 0.77%, 0.79%, 0.68% or 0.71%.

[0049] In the present invention, the specific surface area of ​​the silicon-carbon composite material can be 1-36m 2 / g, such as 2.4, 2.2, 2.7, 3.1, 1.8, 18.6, 21.4, 1.9, 1.8 or 9.6m 2 / g.

[0050] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.

[0051] The present invention also provides an application of the pole piece as described above in an electrochemical device.

[0052] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0053] The reagents and raw materials used in the present invention are commercially available.

[0054] The positive and progressive effects of the present invention are:

[0055] (1) In the present invention, the first template and the manganese source are combined to form a composite template, and pores are formed in the carbon matrix to obtain porous carbon, so that the manganese atoms are distributed in a directional manner in the pores of the porous carbon, which is beneficial to improving the deposition efficiency of silane and gas-phase carbon coating.

[0056] (2) The battery made of the silicon-carbon composite material prepared in the present invention has better cycle performance. DETAILED DESCRIPTION

[0057] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0058] Example 1

[0059] S1. (1) under nitrogen, adding manganese oleate to a 10% aqueous solution of hexadecyltrimethylammonium bromide (CTAB), heating to 60° C., and stirring for 6 h, so that the mass concentration of manganese oleate in the solution is 10%, thereby obtaining a composite template; the mass ratio of CTAB to manganese oleate is 1:1;

[0060] (2) 6930 g of water, 990 g of ethanol, and 40 g of ammonia water were stirred at 800 r / min at 30° C. for 30 min, and then 80 g of resorcinol was added, and the mixture was stirred at 800 r / min at 30° C. for 10 min. Then 120 ml of formaldehyde solution and 20 g of the composite template prepared in the above step (1) were added, and the mixture was stirred at 800 r / min at 30° C. for 24 h. The mixed solution was then transferred to an autoclave, polymerized at 100° C. for 24 h, and centrifuged and dried at 120° C. for 48 h to obtain a carbon matrix.

[0061] (2) The 10 kg carbon matrix prepared above was heated to 800° C. in a rotary kiln for carbonization treatment for 3 h to remove CTAB, then the temperature was raised to 900° C. and 30 L / min of CO2 was introduced for 8 h, then nitrogen was introduced for 30 min to exhaust the CO2 in the furnace, and a hydrogen-nitrogen mixed gas with a gas flow rate of 3 L / min (the volume concentration of hydrogen in the hydrogen-nitrogen mixed gas was 3%) was introduced, and the reduction reaction was carried out for 5 h before discharging the material to obtain porous carbon;

[0062] S2. Add 1 kg of porous carbon prepared above into a rotary kiln with a nitrogen flow rate of 1 L / min and a temperature of 5°C / min. Then, introduce monosilane at a rate of 2 L / min to carry out silane deposition after heating to 500°C and keeping the temperature constant for 12 hours. Then, turn off the silicon source gas and heat to 550°C. Then, introduce 1 L / min of acetylene gas to carry out gas-phase carbon coating. Continue for 4 hours and then cool down and discharge.

[0063] Example 2

[0064] The only difference from Example 1 is that step S1(1) is to add manganese oleate to a 10% CTAB aqueous solution under nitrogen, heat to 60° C., and stir for 6 h to make the mass concentration of manganese oleate in the solution 5%, thereby obtaining a composite template, wherein the mass ratio of CTAB to manganese oleate is 2:1.

[0065] Example 3

[0066] The only difference from Example 1 is that step S1(1) is to add manganese oleate to a 10% CTAB aqueous solution under nitrogen, heat to 60° C., and stir for 6 h to make the mass concentration of manganese oleate in the solution 15%, thereby obtaining a composite template, and the mass ratio of CTAB to manganese oleate is 0.66:1.

[0067] Example 4

[0068] The only difference from Example 1 is that step S1(1) is to add manganese oleate to a 10% CTAB aqueous solution under nitrogen, heat to 60° C., and stir for 6 h to make the mass concentration of manganese oleate in the solution 20%, thereby obtaining a composite template, wherein the mass ratio of CTAB to manganese oleate is 0.5:1.

[0069] Example 5

[0070] The only difference from Example 1 is that step S1(1) is to add manganese oleate to a 6.66% CTAB aqueous solution under nitrogen, heat to 60° C., and stir for 6 h to make the mass concentration of manganese oleate in the solution 10%, thereby obtaining a composite template, and the mass ratio of CTAB to manganese oleate is 0.66:1.

[0071] Example 6

[0072] The only difference from Example 1 is that step S1(1) is to add manganese oleate to a 13.3% CTAB aqueous solution under nitrogen, heat to 60° C., and stir for 6 h to make the mass concentration of manganese oleate in the solution 10%, thereby obtaining a composite template, wherein the mass ratio of CTAB to manganese oleate is 1.33:1.

[0073] Example 7

[0074] The only difference from Example 1 is that step S1(1) is to add manganese oleate to a 15% CTAB aqueous solution under nitrogen, heat to 60° C., and stir for 6 h to make the mass concentration of manganese oleate in the solution 10%, thereby obtaining a composite template, wherein the mass ratio of CTAB to manganese oleate is 1.5:1.

[0075] Example 8

[0076] The only difference from Example 1 is that the CO2 introduction time in step S1(2) is 6 hours.

[0077] Example 9

[0078] The only difference from Example 1 is that the CO2 introduction time in step S1(2) is 12 hours.

[0079] Example 10

[0080] The only difference from Example 1 is that manganese oleate is replaced by MnCl2.

[0081] Comparative Example 1

[0082] The only difference from Example 1 is that the composite template contains only an aqueous solution of manganese oleate with a mass concentration of 10%.

[0083] Comparative Example 2

[0084] The only difference from Example 1 is that the composite template contains only a CTAB aqueous solution with a mass concentration of 10%.

[0085] Comparative Example 3

[0086] The only difference from Example 1 is that no composite template is added.

[0087] Effect Example 1

[0088] The specific surface areas of the porous carbon and silicon-carbon composite materials prepared in the above embodiments or comparative examples were tested using BEST nitrogen adsorption and desorption equipment.

[0089] The silicon-carbon composite materials obtained in the above-mentioned embodiments or comparative examples were tested for Mn content using an inductively coupled plasma (ICP) analyzer. The test method is as follows: (1) Pre-treatment by microwave digestion, 0.5 g of the silicon-carbon composite materials obtained in the embodiments or comparative examples were placed in a digestion tank, 3 mL of concentrated nitric acid and 9 mL of concentrated sulfuric acid were added in sequence using a liquid adder, and the mixture was shaken well; and the mixture was kept at a constant temperature of 160°C for 3 min, 180°C for 3 min, 200°C for 10 min, and 220°C for 10 min, and then cooled to room temperature, filtered using quantitative filter paper, and the filtrate was placed in a 50 mL volumetric flask as the test solution; (2) the above test solution was placed in a PerkinElmer ICP spectrometer Avio TM The test was carried out in 200 equipment; the test condition was an air pressure of 2.5MPa.

[0090] The results are shown in Table 1.

[0091] Table 1

[0092] Specific surface area of ​​porous carbon m2 / g Specific surface area of ​​silicon-carbon composite material m2 / g Mn content% Example 1 1811 2.4 0.74 Example 2 1824 2.2 0.31 Example 3 1807 2.7 0.94 Example 4 1795 3.1 1.21 Example 5 1487 1.8 0.69 Example 6 2015 18.6 0.65 Example 7 2088 21.4 0.77 Example 8 1701 1.9 0.79 Example 9 1664 1.8 0.68 Example 10 1703 9.6 0.71 Comparative Example 1 1473 1.7 0.11 Comparative Example 2 1789 11.2 0 Comparative Example 3 1484 1.4 0

[0093] Note: Mn content % means the percentage of the mass of Mn to the mass of the silicon-carbon composite material.

[0094] Effect Example 2

[0095] A mixture of the silicon-carbon composite material, a binder (sodium carboxymethyl cellulose, CMC; styrene-butadiene rubber, SBR) and a conductive agent (conductive carbon black, SP; single-walled carbon nanotube, SWCNT) prepared in the above embodiment or comparative example (wherein the mass ratio is, silicon-carbon composite material: SP: SWCNT: CMC: SBR = 90: 4.5: 0.5: 2.5: 2.5) is homogenized and coated on a copper foil, and vacuum dried, rolled and cut to obtain a negative electrode sheet. A metal lithium sheet is used as a counter electrode, and the electrolyte ratio is 1M LiPF6, 89% by volume of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio of 1: 1), 10% by volume of fluoroethylene carbonate (FEC) and 1% by volume of vinylene carbonate (VC), and a polypropylene microporous membrane is used as a diaphragm, and a button-type half-cell is assembled in an inert gas glove box system filled with argon.

[0096] At 25°C, the assembled half-cell was tested for charge and discharge cycles using a blue electric test instrument to obtain data such as its reversible specific capacity, first coulombic efficiency, and cycle. The test procedure was 0.1C discharge to 5mV, 0.05C discharge to 5mV, 0.1C charge to 2V. The cycle format was: 0.5C discharge to 5mV, 0.05C discharge to 5mV, 0.5C charge to 1V.

[0097] The results are shown in Table 2.

[0098] Table 2

[0099] Reversible specific capacity mAh / g First coulombic efficiency % 500 cycles retention rate % Example 1 1788 93.0 92.2 Example 2 1812 88.7 90.7 Example 3 1694 92.7 90.5 Example 4 1676 89.4 87.9 Example 5 1913 92.3 84.1 Example 6 1654 88.5 85.2 Example 7 1546 86.5 87.0 Example 8 1768 93.1 88.2 Example 9 1657 91.3 84.4 Example 10 1713 86.2 87.1 Comparative Example 1 1870 82.4 82.1 Comparative Example 2 1694 84.7 82.2 Comparative Example 3 1703 85.1 76.7

[0100] It can be seen from Table 2 that, compared with Comparative Examples 1-3, in Examples 1-10, porous carbon is obtained by forming pores on the carbon matrix under the composite template (the first template and the manganese source), which can make the manganese atoms directional in the pores of the porous carbon, and is beneficial to improve the deposition efficiency of silane and gas-phase carbon coating, so that the battery assembled with the silicon-carbon composite material prepared in Examples 1-10 has better cycle performance and first coulombic efficiency.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1. Carbonizing and reducing the mixture A in sequence to obtain porous carbon; the mixture A comprises a carbon matrix and a composite template; the composite template comprises a mixed solution of a first template and a manganese source; the specific surface area of ​​the porous carbon is 1600-2200 m 2 / g; S2. sequentially subjecting the porous carbon to silane deposition and vapor phase carbon coating.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: In A and S1, the manganese source is manganese oleate and / or manganese chloride, such as manganese oleate or manganese chloride; B. In S1, in the composite template, the mass concentration of the first template is 6%-15%, preferably 6.66%-14%, for example 9%, 10%, 11% or 13.3%; In C and S1, in the composite template, the mass concentration of the manganese source is 5%-20%, preferably 8%-12%, for example 9%, 10% or 11%; In D and S1, in the composite template, the mass ratio of the first template to the manganese source is (0.5-2):1, preferably (0.66-1.5):1, for example 1:1 or 1.33:

1.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: In A and S1, the type of the carbon matrix includes phenolic resin and / or asphalt, such as phenolic resin; In B and S1, the type of the first template includes one or more selected from Pluronic F-127, Synperonic F-108, Pluronic F-68, hexadecyl trimethyl ammonium bromide and sodium dodecyl sulfate, such as hexadecyl trimethyl ammonium bromide; In C and S1, the mass ratio of the carbon matrix to the composite template is (300-700):1, for example, 400:1, 500:1 or 600:1; D. In S1, the temperature of the carbonization treatment is 600-1000°C, such as 700, 800 or 900°C; In E and S1, the carbonization treatment time is 1-5 hours, for example, 3 hours; F. In S1, after the carbonization treatment and before the reduction reaction, a step of carbon dioxide activation is also included; In G and S1, a reducing agent is added during the reduction reaction; the type of the reducing agent is, for example, a hydrogen-nitrogen mixed gas; in the hydrogen-nitrogen mixed gas, the volume concentration of hydrogen is preferably 1%-5%, for example, 3%; In H and S1, the mass volume ratio of the carbon matrix and the reducing agent is 10 kg: (20-30) L, for example, 10 kg: 27 L; In I and S1, the reduction reaction time is 3-7 h, for example 5 h; In J and S1, the specific surface area of ​​the porous carbon is 1650-2100m 2 / g, such as 1811, 1824, 1807, 1795, 1487, 2015, 2088, 1701, 1664, or 1703m 2 / g.

4. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: In A and S1, when the carbon matrix is ​​a phenolic resin, the preparation method of the phenolic resin comprises the following steps: mixing resorcinol, formaldehyde, ammonia water, ethanol and water, and performing a polymerization reaction; The mass volume ratio of the resorcinol to formaldehyde is preferably 80 g: (100-140) mL, for example 80 g: 120 mL; the mass ratio of the resorcinol to the aqueous ammonia is preferably (1-3): 1, for example 2: 1; the mass ratio of the resorcinol to the ethanol is preferably (70-90): 990, for example 80: 990; the mass ratio of the resorcinol to the water is preferably 80: (6500-7500), for example 80: 6930; the temperature of the polymerization reaction is preferably 90-110° C., for example 100° C.; the time of the polymerization reaction is preferably 20-30 h, for example 24 h; In B. S1, the temperature of carbon dioxide activation is 800-1000°C, for example, 900°C; In C and S1, when the carbon dioxide is activated, the flow rate of the carbon dioxide is 20-40 L / min, for example, 30 L / min; In D and S1, the activation time of the carbon dioxide is 6-10 hours, for example 8 hours; In E and S1, the mass volume ratio of the carbon matrix and the carbon dioxide is 1 g:(1-2) L, for example, 1 g:1.44 L.

5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: In A and S2, the temperature of the silane deposition is 400-600° C., for example, 500° C.; In B and S2, the silane deposition time is 10-14 h, for example 12 h; In C and S2, the rate of heating from room temperature to the temperature of silane deposition is 3-7°C / min, for example, 5°C / min; In D and S2, the mass volume ratio of the porous carbon and the silane gas deposited by the silane is 1 g: (1-2) L, for example, 1 g: 1.44 L; In E and S2, the temperature of the gas phase carbon coating is 400-600°C, for example, 550°C; In F and S2, the gas phase carbon coating time is 2-6 hours, for example, 4 hours; In G and S2, the mass volume ratio of the porous carbon and the carbon source gas coated with the gas phase carbon is 1g:(0.1-1)L, for example, 1g:0.24L.

6. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 1 to 5.

7. A silicon-carbon composite material, characterized in that: It has a core-shell structure, comprising a core and an outer shell, wherein the outer shell covers the core; the core comprises porous carbon, silicon and manganese; the specific surface area of ​​the porous carbon is 1600-2200m 2 / g; the silicon and manganese are distributed in the pores of the porous carbon; and the shell includes a carbon coating layer.

8. The silicon-carbon composite material according to claim 7, characterized in that: The silicon-carbon composite material meets one or more of the following conditions: A. The specific surface area of ​​the porous carbon is 1650-2100m 2 / g, such as 1811, 1824, 1807, 1795, 1487, 2015, 2088, 1701, 1664, or 1703m 2 / g; B. In the silicon-carbon composite material, the mass content of manganese is 0.3%-1.5%, for example, 0.74%, 0.31%, 0.94%, 1.21%, 0.69%, 0.65%, 0.77%, 0.79%, 0.68% or 0.71%; C. The specific surface area of ​​the silicon-carbon composite material is 1-36m 2 / g, such as 2.4, 2.2, 2.7, 3.1, 1.8, 18.6, 21.4, 1.9, 1.8 or 9.6m 2 / g.

9. A pole piece, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 6 to 8.

10. Use of the electrode piece according to claim 9 in an electrochemical device.

Citation Information

Patent Citations

  • Lithium-ion battery graphitized mesoporous carbon / silicon composite anode materials and preparation method thereof

    CN102456876A

  • Self-assembly preparation method of spherical manganese-lithium silicate composite material and anode composition

    CN106784616A

  • Silicon-based composite material and preparation method thereof, negative electrode material and lithium battery

    CN108807862A

  • Silicon-carbon negative electrode composite material, preparation method and application thereof, and battery

    CN117790738A

  • Submicron silicon-carbon composite material containing manganese-oxygen heterojunction particles, preparation of submicron silicon-carbon composite material and application of submicron silicon-carbon composite material in lithium ion battery

    CN117936746A